Structural violence and the need for compassionate use of methadone in Mexico - Martha Romero-Mendoza; Ingris Peláez-Ballestas; Ariagor Manuel Almanza-Avendaño; Emilia Figueroa (BMC, 2022)
Abstract Background Epidemiological data from Mexico have documented an increase in heroin use in the last decade. However, there is no comprehensive care strategy for heroin users, especially those who have been accused of a crime. The objective of this study was to describe the heroin and methadone use of intravenous heroin users of both sexes who have been in jail, to offer evidence for the formulation of health policy. Methods This study used an ethnographic approach, with open-ended interviews carried out from 2014 to the present. Heroin users of both sexes attending a private methadone clinic in Mexico City were invited to participate. The sample was non-probabilistic. All interviews were audiotaped and transcribed, and narratives were analyzed using thematic analysis. Results Participants in this study were 33 users of heroin, two of them women, who had been in prison. They ranged in age from 33 to 62 years, had used heroin for a period of 13-30 years, and were from three states: Michoacan, Oaxaca, and Mexico City. Three principal categories of analysis were structured: 1. Pilgrimage for help (dynamics of the drama of suffering, pain, and time through health care spaces); 2) methadone use as self-care; and 3) accessibility to methadone treatment. The impossibility of access to methadone treatment is a condition which motivates users in their journey. The dynamics of methadone use are interpreted as a form of self-care and care to avoid substance use. Reducing the psychological, physical, and harmful effects of the substance allows them to perform daily activities. The inability to access treatment leads to a significant effect on users who experience structural violence. Conclusion Compassionate methadone treatment and holistic attention should be considered as a way to meet patients' needs and mitigate their suffering, based on public health policy that allows for human rights-based care.